Fatal acute liver failure following norovirus gastroenteritis in a child: A case report - Rabab Taha; Noura Elazhary; Sarah Alqhtani; Walaa Almansouri (Journal of Infection and Public Health)
Norovirus is the leading cause of acute gastroenteritis and rarely present with extra-intestinal manifestations. There are few reported cases of hepatitis following norovirus gastroenteritis, with no documented fatalities. We present a case of fatal acute hepatitis following norovirus gastroenteritis in a child. The patient was a previously healthy 6-year-old boy who presented with diarrhea, vomiting, and fever. He was admitted and treated supportively as a case of acute gastroenteritis. Despite treatment, he rapidly developed acute liver failure in the course of gastroenteritis. Other potential causes including drugs and other possible viral infections were ruled out, only norovirus was isolated from his stool. The patient’s liver function continued to deteriorate leading to fulminant liver failure and death within days.